Color in motion: Generating 3-dimensional multispectral models to study dynamic visual signals in animals - Miller, Audrey E.; Hogan, Benedict G.; Stoddard, Mary Caswell (Frontiers in Ecology and Evolution, 2022)
Analyzing color and pattern in the context of motion is a central and ongoing challenge in the quantification of animal coloration. Many animal signals are spatially and temporally variable, but traditional methods fail to capture this dynamism because they use stationary animals in fixed positions. To investigate dynamic visual displays and to understand the evolutionary forces that shape dynamic colorful signals, we require cross-disciplinary methods that combine measurements of color, pattern, 3-dimensional (3D) shape, and motion. Here, we outline a workflow for producing 3D models with objective color information from museum specimens. The workflow combines multispectral imaging with photogrammetry to produce 3D models that contain calibrated ultraviolet (UV) and human-visible (VIS) color information and incorporate pattern and 3D shape. These models can subsequently be animated to incorporate both signaler and receiver movement and analyzed with a variety of receiver-specific visual models. This approach—which can be flexibly integrated with other tools and methods—represents a key first step toward analyzing visual signals in motion. We describe several timely applications of this workflow and next steps for multispectral 3D modeling and animation techniques.